BORDER CROSSING INTIMATION TO SOLDIERS FROM CAMP USING RECEIVED SIGNAL STRENGTH INDICATION. - Swetha.G, Sivagami.K, Srikala.V,Dr.Devaraju.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Security of a nation depends on its Army and the efficiency of its army depends on it soldiers. For an indestructible army, the soldier’s security is the most important factor to achieve and maintain National security. Our project mainly focuses on a system which can identify border to protect our soldier. The existing projects are not powerful enough to prevent the soldiers from crossing the border as it only gives the data about the border but not about the exact distance that the soldier has travelled from the border. In our project the technology of Received Signal Strength Indication (RSSI) is used which indicates the power level received by the antenna, this information is used to provide geographic location of soldiers with respect to the border. The proposed systems receiver’s section includes ARDUINO MEGA microcontroller, ESP8266 RSSI module, Audio Playback Recorder (APR) voice alert circuit, Liquid Crystal Display (LCD) and Global System for Mobile Communication (GSM) module. The transmitter’s section includes mobile phone, ESP8266 RSSI module. The Soldier gets continuous updates about his zone, when the soldier goes out of reachable zone, he can alert the base station for help using GSM module.